Design of high-order QAM modem algorithm. Issue 4 (April 2021) - Chang, Yinghui; Liu, Changlong
Abstract: More and more attention has been paid on the issue of bandwidth utilization. Nowadays, with limited frequency spectrum resources, the capacity of traditional communication system has not been able to meet the demands of users. Quadrature Amplitude Modulation (QAM) has become a critical technical solution for broadband wireless access and wireless video communication due to its advantages of high frequency spectrum utilization and high-power spectrum density. In order to further improve the control information transmission performance of high-order QAM, we propose a high-order QAM modulation and demodulation algorithm, which is designed from the aspects of interleave between channels, leading sequence, constellation modulation, frequency domain sampling and (Orthogonal Frequency Division Multiplexing) OFDM generation, etc. The simulation results demonstrate that the algorithm can ensure the reliable reception of control information.